Parti Islam Se-Malaysia (Pas) in Malaysia Politics: A History of Tuan Guru Nik Aziz’s Scholarship and Leadership in Establishing an Islamic State in Kelantan - Muhammad Syahir Bin Md Ali; Imtiyaz Yusuf (Universitas Islam Negeri Mataram, 2021)
The study seeks to examine the brief history of political Islam in Malaysia with a focus on Pan-Malaysian Islamic Party/Parti Islam Se-Malaysia (PAS). The emergence of PAS in the early 1950s marks the beginning of the involvement of Islamic Movements in politics as a platform for the revivalism of Islam in the region. In addition, the role of PAS leaderships also briefly discussed with a great emphasis on the leadership of PAS political maestro, Tuan Guru Nik Aziz bin Nik Mat. His piety in Islam is translated into his political thought which are influential during his involvement in politics. Tuan Guru’s upbringing and his education background had biggest influence towards his worldview on politics. This study described his contribution on Islam and in Malaysian politics, especially his grand idea on the establishment of Islamic state in Kelantan. The idea of ideal Islamic model of a state was established in Kelantan. It is in line with his perspective of how a society should operate and the functions of government in micro-managing the society. As a conclusion, Tuan Guru Nik Aziz plays an important role within PAS and to the establishment of the model of Islamic State in Kelantan.